ANALISIS PENGGUNAAN GOOGLE GEMINI TERHADAP PROSES PEMBELAJARAN MAHASISWA - Putri Afiqah Binti Ahmad; Muhammad Irwan Padli Nasution (Kampus Akademik Publiser, 2025)
This research analyzes the role of Google Gemini, a new artificial intelligence (AI) technology from Google, in supporting students' learning process. Google Gemini offers an AI solution that is able to process various data formats and provide information contextually and quickly. This research uses descriptive qualitative method to explore the impact of Google Gemini on information access, learning personalization, and enhancing students' critical skills. The results show that the use of Google Gemini has a positive impact on learning effectiveness, increasing the speed of comprehension, learning independence, critical thinking skills, and student collaboration. With its interactive features, Google Gemini helps students in completing academic tasks efficiently and deeply. This technology is expected to contribute to improving the quality of student education in an increasingly complex digital era.